Wage Flexibility and Openness - Aizenman, Joshua (Quarterly Journal of Economics, 1985)
This paper analyzes the degree of short-run, real wage flexibility in a two-sector economy under floating rates. This is done by deriving optimal wage indexation in a contracting framework. We find that the more closed the economy, the lower the degree of wage indexation. As a result, output will fluctuate less around its desired level in a more closed economy. These findings further imply that a given unexpected monetary shock will cause as maller output shock in a more open economy, whereas a given real shock will induce a smaller output shock in a more closed economy.